The Unmasking Effect: Propofol-Induced Brugada Pattern in a Critically Ill Patient - Esiemoghie Akhigbe; Ebubechukwu Ezeh; Benjamin Dao; Kelechukwu Okoro; Paul Okhumale (Case Reports in Cardiology)
Brugada syndrome is a known cause of dysrhythmias and sudden cardiac death. It is linked to mutations in myocardial sodium channel leading to hyperexcitable cardiac myocytes. The use of this sedative has been linked to the development of inducible Brugada via blockade of sodium currents in cardiac myocytes. Although propofol is usually avoided in patients with known Brugada syndrome, some patients might have undiagnosed Brugada syndrome and thus are at risk for complications. We present a case of propofol induced Brugada in a critically ill patient.